Molecular dynamics simulations of primary damage formation and tensile properties of irradiated Cu–Ni binary alloys - Xiao-Ping Wei; Hairui Li; Yaling Zhang; Xue Li; Chen Li (Journal of Materials Research and Technology)
Cu–Ni alloys are widely used in high-performance applications, such as in nuclear reactors, spacecraft, and other extreme environments, due to their excellent mechanical properties. However, under extreme irradiation conditions, these alloys undergo significant degradation in their microstructure and mechanical properties, which affects their long-term performance. This study investigates the effects of irradiation on the microstructure and mechanical properties of Cu–Ni alloys using molecular dynamics (MD) simulations, focusing on the displacement cascade process under varying temperatures, Primary Knock-on Atom (PKA) energies, crystal orientations, and Ni contents. The results show that higher temperatures facilitate the recombination of interstitial atoms and vacancies. Thereby reducing the number of Frenkel defect pairs in the steady state, while increasing PKA energy significantly increases the number of defect pairs due to more intense cascade collisions. Additionally, the study shows that defects exhibit different behaviors in the [100], [110], and [111] orientations, highlighting the anisotropic nature of Cu–Ni alloys. Tensile simulations indicate that although irradiation reduces the yield strength of Cu–Ni alloys, alloys with higher Ni content exhibit a smaller decrease in yield strength, especially after irradiation, suggesting that increasing Ni content plays a significant role in enhancing the alloy's irradiation resistance and maintaining mechanical performance under irradiation conditions. This study explores the effects of temperature, PKA energy, crystal orientation, and Ni content on irradiation-induced damage in Cu–Ni alloys, aiding the development of radiation-resistant materials and providing a theoretical foundation for improving the mechanical stability and performance of materials used in extreme irradiation environments.